Glycogen Storage Disorder (Medical Forum Monthly, 2024)
Glycogen Storage Disease (GSD, also called Glycogenosis and Dextrinosis) is the result of defects in the processing of glycogen synthesis or breakdown within muscles, liver, and other cell types. Patients usually present with low blood sugar, enlarged liver, slow growth, muscle cramps, seizures and anemia. Von Gierke disease is the most common type of glycogen storage disorder. Von Gierke[1] described the first patient with GSD type I in 1929 under the name hepatonephromegalia glycogenica. In 1952, Cori and Cori [2] demonstrated that glucose-6-phosphatase (G6Pase) deficiency was a cause of GSD type I. Other types are Pompe, Forbes, Cori, Hers and Anderson types.GSD type 5 McArdle disease affects skeletal muscles [3].